2012
DOI: 10.1590/s1413-35552012005000026
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and reliability analysis of the Brazilian version of Pediatric Balance Scale (PBS)

Abstract: Background: The Pediatric Balance Scale (PBS) was developed from a modified version of the Berg Balance Scale aiming to obtain a balance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 23 publications
1
27
0
9
Order By: Relevance
“…A total of 14 functional balance tests were identified that were investigated in children . These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 14 functional balance tests were identified that were investigated in children . These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified.…”
Section: Resultsmentioning
confidence: 99%
“…These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified. A detailed description of the test modalities for each test is available in Appendix S1 (supporting information published online).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Versão brasileira da escala de Equilíbrio Pediá-trica, adaptada transculturalmente e validada 10 11 avalia o equilíbrio dinâmico, que é definido como a distância máxima possível de atingir, além do comprimento do membro superior, mantendo-se a base de apoio fixa. A fita métrica foi fixada na parede, na altura do processo acrômial do membro superior dominante da criança, com ombro em 90° de flexão (anterior) e abdução (direita e esquerda) 11,12 .…”
Section: Escala De Equilíbrio Pediátricaunclassified